Application of QM/MM and QM methods to investigate histone deacetylase 81. Issue 3 (9th March 2015) - Gleeson, Duangkamol; Gleeson, M. Paul
<x xml:space="preserve">Abstract</x> Computational chemistry plays an important supporting role in the early stages of drug discovery research.